Rare Case Report On Median Arcuate Ligament Syndrome – A Surgical Approach - Amrutha Gopal; Rubina Mariam Oommen (International Journal of Pharmacy and Analytical Research, 2024)
Median Arcuate Ligament Syndrome (MALS), also known as celiac artery compression syndrome or Dunbar syndrome, is a rare vascular disorder characterized by compression of the celiac artery by the median arcuate ligament. This compression can lead to a range of symptoms including postprandial abdominal pain, weight loss, nausea, and vomiting. We present a case of a 57-year-old female patient who presented with complaints of left hypochondrial and left lumbar pain. Her medical history was significant for newly diagnosed diabetes and bilateral salpingo-oophorectomy. Upon further evaluation, CT abdomen revealed narrowing of the celiac trunk due to an overlying thickened median arcuate ligament, confirming the diagnosis of MALS. Surgical management was pursued with the laparoscopic-assisted release of the median arcuate ligament under general anesthesia. The procedure successfully decompressed the celiac trunk, alleviating the patient's symptoms. Postoperatively, the patient had an uneventful recovery and was discharged with general instructions. This case underscores the importance of recognizing MALS in patients presenting with characteristic symptoms and the efficacy of surgical intervention in providing relief and improving quality of life.